Causal Factors of the International Emigration of Ecuadorians: Represented in the Chronicles (Docentes 2.0 Journal, 2024)
There is a significant corpus of chronicles related to the international emigration of Ecuadorians, which represent stories of people who lived nearly two centuries of republican life caused by droughts, earthquakes, and other natural phenomena that have hit the country. The objective of this essay was to theorize, describe, and analyze the causes that determine and contribute to the international emigration of Ecuadorians by what is represented, recreated, and evidenced in six works of chronicles on migration, which have been selected as the object of study. The academic work was developed with the orientation of the inductive method in the humanistic paradigm, with a qualitative, interpretive approach and topical narrative design. Furthermore, with the advent of the feminization of international emigration originating in Ecuador, various factors have been identified that prompted Ecuadorian women to emigrate, such as family and relationship problems that definitively influence their decision, the search for educational opportunities abroad such as postgraduate studies in prestigious universities, the aspiration to expand new horizons of professional improvement and personal fulfillment and the need to demonstrate a sexual orientation that does not correspond to what is considered normal in Ecuador. And that it remained hidden in the country of origin. These realities constitute the causes behind migration and reveal a phenomenon that has affected the country's social structure.
Keywords: Emigration; causes; chronic